The Effectiveness of Kahoot! Based on Local Wisdom to Improve Creative Thinking Skill and the Spirit of Nationality of Students in Islamic Elementary School - E. Kus Eddy Sartono; Sukowati Sukowati; Siti Soleha (UIN Siber Syekh Nurjati Cirebon, 2021)
AbstractThe goal of this research is to see how successful the Kahoot game! based on local wisdom is at boosting students' creative thinking capabilities and national spirit. This is a quasi-experimental study that uses technical data analysis, such as the t-test and MANOVA test, with SPSS as a supporting tool. Tests and questionnaires that had been validated by instrument specialists, class teachers, and peers were used to collect data. The participants in this study were fifth-grade students from an Islamic elementary school, with a total of 81 pupils. The results showed a significant level of 0.000 < 0.05, indicating that fifth-grade students in a Islamic elementary school who are taught using the Kahoot game!! have a considerable comprehension of the ability to think about national characters compared to children who are not taught using the Kahoot game. The Kahoot! game based on local wisdom has a substantial impact on enhancing children's creative thinking skills and nationalism in Islamic elementary school, according to the findings.Keywords: kahoot! game based on local wisdom, creative thinking skill, the spirit of nationality.Â AbstrakPenelitian ini bertujuan untuk mengetahui tingkat efektifitas game kahoot! berbasis kearifan lokal dalam meningkatkan kemampuan berpikir kreatif dan karakter semangat kebangsaan siswa. Penelitian ini merupakan penelitian quasi experiment dengan menggunakan teknis analisis data menggunakan uji t dan uji MANOVA dengan berbantuan SPSS. Pengumpulan data dilakukan melalui pretest-posttest dengan menggunakan tes dan angket yang telah divalidasi oleh ahli instrumen, guru kelas, dan teman sejawat. Subjek penelitian ini yaitu siswa kelas V madrasah ibtidaiyah yang berjumlah 81 siswa. Hasil penelitian yang diperoleh menunjukkan taraf signifikansi 0,000 < 0,05 artinya ada perbedaan signifikan kemampuan berpikir kreatif dan karakter semangat kebangsaan siswa kelas V madrasah ibtidaiyah yang diajar menggunakan game kahoot! dan siswa yang tidak diajar dengan menggunakan game kahoot!. Sehingga dapat disimpulkan bahwa game kahoot! berbasis kearifan lokal berpengaruh signifikan dalam meningkatkan kemampuan berpikir kreatif dan semangat kebangsaan siswa di madrasah ibtidaiyah/sekolah dasar.Kata kunci: game kahoot! berbasis kearifan lokal, keterampilan berpikir kreatif, semangat kebangsaan.